HUBUNGAN KEMAMPUAN MEMBACA DENGAN KETERAMPILAN MENULIS PADA MATA PELAJARAN BAHASA INDONESIA KELAS II DI MI ASSUNNIYYAH TAMPUNANG - Nor Hikmah; Rahmawati (Lubna : Journal of Islamic Elementary Education, 2025)
Indonesian language learning plays a crucial role in primary education as it serves as a means to develop language skills, which encompass four main aspects: listening, speaking, reading, and writing. Among these skills, reading and writing are closely interrelated written language skills that significantly contribute to the development of students’ thinking ability, creativity, and communication skills. This study aims to analyze whether there is a relationship between reading ability and writing skills in Indonesian language lessons among second-grade students at MI Assunniyyah Tampunang. The research method employed is correlational with a quantitative approach. The subjects of this study included all second-grade students at MI Assunniyyah Tampunang, totaling 14 students, making this study a population-based research. The data analysis in this study employed the Product Moment correlation technique. The results of the Pearson Product Moment correlation test yielded a correlation index of rxy=0.344r_{xy} = 0.344rxy​=0.344. This value was then compared with the critical value from the correlation table (rtable=0.339r_{table} = 0.339rtable​=0.339) at a 5% significance level, resulting in rxy=0.344>rtable=0.339r_{xy} = 0.344 > r_{table} = 0.339rxy​=0.344>rtable​=0.339. These findings indicate a significant relationship between reading askills and writing skills in the Indonesian language subject. This is evidenced by the fact that students with lower reading ability also tend to demonstrate lower writing skills.   Keywords: Reading Skills; Indonesian Writing Skills